Perancangan Media Pembelajaran Interaktif untuk Sistem Pernapasan Manusia - Rani Puspita Dhaniawaty; Annisa Paramitha Fadilah (Jurnal Teknologi Informasi dan Pendidikan, 2021)
The purpose of this research is to assist teachers in averaging the delivery and explanation of the human respiratory system. Besides, it can help improve the quality of student learning and help students to carry out the learning process independently. This study used an Object-Oriented Analysis Design (OOAD) system approach, a system design tool using Unified Modeling Language (UML), and a system development method using the ADDIE method. The results of this research are the design of instructional media in the form of analysis and design (storyboard) interactive multimedia applications containing material about the human respiratory system presented in the form of audio, video, and animation. In addition, the design of this interactive learning media application helps teachers in equating the delivery and explanation of the subject matter, can improve the quality of student learning, help students to carry out the learning process independently. With the design of this interactive learning media application, it can provide an overview to teachers and students about interactive learning media of the human respiratory system that can help the teaching and learning process